Electromyographic evaluation of the lower limbs of patients with Down syndrome in hippotherapy - Mariane Fernandes Ribeiro; Ana Paula Espindula; Alex Abadio Ferreira; Luciane Aparecida Pascucci Sande de Souza; Vicente de Paula Antunes Teixeira (Universidade Estadual de Maringá, 2017)
Hippotherapy is a therapeutic method that uses the horse's movement to achieve functional results in practitioners with Down syndrome (DS), who present motor and neurophysiological changes that affect the musculoskeletal system. Evaluating the motor behavior related to the control and the improvement of muscle activation in practitioners with Down syndrome subjected to hippotherapy. 10 practitioners were divided into two groups: Down Group (DG) - practitioners with DS, and Healthy Group (HG) - practitioners with no physical impairment. The muscles gluteus medius, tensor fasciae latae, rectus femoris, vastus medialis, vastus lateralis, biceps femoris, tibialis anterior and gastrocnemius were evaluated by electromyography using gross RMS values, which correspond to muscle activation; the evaluations were performed on the 1st and 10th hippotherapy sessions (frequency: once a week), and after 2 months interval without treatment, they were performed on the 1st and 10th hippotherapy sessions (frequency: twice a week). It was noted that activation of the studied muscles increased with the passing of sessions, regardless the weekly frequency of attendance; however, the period without treatment resulted in reduction of this effect. Practitioners with DS presented satisfactory changes in muscle activation pattern, in learning and in motor behavior during hippotherapy sessions.